17th Street Fork & Knife / Ahmad Zulhakim Azhar … [et al.] - Azhar, Ahmad Zulhakim; Mohamad Nazarruddin, Nur Athirah; Rozman, Nurul Aiman; Azlan, Noraqilah; Saleh, Nadhilah (2021)
17th Street Fork and knife is a company that opens a restaurant which has the concept of western food. This business is a form by partnership which consists of five members. Overall, we plan to start this business by loan which costs RM322,861. It will be located at 36, Lorong Rahim Kajai 14, Taman Tun Dr Ismail, 60000 Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur and will be operating on 1st March 2021. This is a manufacturing type of company which will produce and serve quality western food to our beloved customers. Hence, we chose Klang Valley as our main business location because we have considered many factors and it is a strategic place to start a business. We choose to sell this kind of food because we want to give a different vibe of food taste to the population nearby. For our motto is “A healthy food, for a wealthy mood”, we want to make sure that buyers will satisfy and will repeat ordering our services and foods. Our food is suitable for all ages especially working people because it can be prepared in a short time. The services can help them to reduce waiting time due to busy roads at lunch time. Our services also will satisfy many customers to keep coming to our restaurant. It is because the staff that work in this restaurant are enough to serve the customers who come here. The menu that we serve is guaranteed from Halal sources which are raw materials or other ingredients, so people from different kinds of religion or culture can stop by and try our foods without any doubt. The prices that we provided are also affordable to buy.